ORIF versus nailing for humeral shaft fractures: A meta-analysis and systematic review of randomised clinical trials and observational studies. (28th May 2021) - van de Wall, B; van Veelen, N; Babst, R; Link, B; Knobe, M; Beeres, F
Abstract: Objective: This meta-analysis aims to compare open reduction and internal fixation with a plate (ORIF) versus nailing for humeral shaft fractures in terms of healing, complications, general quality of life and shoulder/elbow function. Methods: PubMed/Medline/Embase/CENTRAL/CINAHL was searched for both randomised clinical trials (RCT) and observational studies comparing ORIF with nailing for humeral shaft fractures. Effect estimates were pooled across studies using random effects models and presented as weighted odds ratio (OR) or risk difference (RD) with corresponding 95% confidence interval (95%CI). Subgroup analysis was performed stratified by study design (RCTs and observational studies). Results: A total of ten RCT's (525 patients) and eighteen observational studies (4906 patients) were included. The effect estimates obtained from observational studies and RCT's were similar in direction and magnitude. More patients treated with nailing required re-intervention (RD: 2%; OR 2.0, 95%CI 1.0 – 3.8) with shoulder impingement being the most predominant indication (17%). Temporary radial nerve palsy secondary to operation occurred less frequently in the nailing group (RD: 2%; OR 0.4, 95% CI 0.3 – 0.6). Notably, all but one of the radial nerve palsies resolved sponta-neously in each groups. Nailing leads to a faster time to union (mean difference: -1.9 weeks, 95%CI -2.9 – -0.9), lower infection rate (RD: 2%; OR: 0.5, 95%CI 0.3 – 0.7) and shorter operation duration (mean difference: -26 minutes, 95%CI -37 – -14). No differences were found regarding non-union, general quality of life, functional shoulder scores, and total upper extremity scores. Conclusion: Nailing carries a lower risk of infection, postoperative radial nerve palsy, shorter operation duration, and time to union. Absolute differences, however, are small and almost all patients with radial nerve palsy recovered spontaneously. Satisfactory results can be achieved with both treatment modalities and both techniques have their inherent pros and cons.